COVID-19 crisis and stock market volatility in Nigeria: A GARCH model approach - Onuorah Anastasia, C; Ehiedu Victor, C; Ezekiel, Okoh (International research journal of management, IT and social sciences, 2022)
The economic downturns locally and internationally due to the COVID-19 crisis were the main motivation for this study. However, rather than broadly examining economic indices, this paper focused on the reaction of the Nigerian stock market in terms of volatility to the crisis. The specific objectives of the study were to identify differences in market performance due to the COVID crisis, determine volatility persistence and ascertain the leverage effects of the news on stocks on the stock exchange floor. Adopting an ex-post facto research design, monthly time-series All-Share Index data were analyzed using descriptive statistics, GARCH(1,1), and EGARCH models. It was found that volatility existed in the market during the COVID-19 crisis however volatility persistence was low. EGARCH results showed asymmetric parameters did not exist revealing the form of leverage effect COVID-19 posed to the market. The market thus had identical responses to both bad and good news of COVID-19 announcements of the same magnitude. It was recommended that regulatory authorities and policymakers be proactive in their approach to forecasting market performance to reduce the negative effects of bad news on market indices.